Rational Thinking Of Harun Nasution: The Renewal Of Islamic Moral Education In Indonesia - yusuf, safwa (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2024)
Education aims to realize the perfection of civilization and human dignity. Education is also always in process and undergoing renewal according to the time required, all with a standard that produces good intellectual, moral, and spiritual qualities for students. Harun Nasution (1919-1998), as the object of this literature research, had progressive ideas and contributions regarding moral education in Islamic education reform, both in his thought arguments and in the development of institutions. This was confirmed when he was at IAIN Syarif Hidayatullah Jakarta by getting used to rational, scientific reform thinking to grow and develop at the Islamic University. In arguing for renewal, Harun emphasizes the importance of a sensible attitude in strengthening moral education so as not to be trapped in traditional thinking. Therefore, every ritual and other religious obligation taught in educational institutions must not be interpreted only as knowledge ordered according to law and its formal form but must aim to realize noble moral development. Therefore, the main instrument in building moral education for Harun Nasution is always to use ratio and heart to maintain balance in life. Students are seen as righteous when they understand that thinking or reasoning is the task of science, honing morals, and the heart is a religious task, but both must have a balance. The creation of spiritual and physical balance indicates upholding moral education. On the other hand, social inequality will occur when the balance of knowledge and morals is lost. Keywords : Harun Nasution, moral education, rational thinking.